PENGARUH KEGIATAN MARKETING TERHADAP PROFITABILITAS DAN NILAI PASAR DI PERUSAHAAN PERBANKAN - Daniel, Tri (Business Accounting Review, 2015)
This study was to determine whether there are significant implementation of Marketing Expense, Company age, and Company Size on profitability and Market value. Samples used in this study were 28 companies in the banking sector with the research period 2009-2013 using multiple regresion. The results of this study prove that the Marketing Expense have significant positive effect on Profitability (ROS) and Market Value (MTBV & Tobins Q). Company Age also negatively affect ROS. Company Size has a significant positive effect on Profitability (ROA) and Market Value (Tobins Q)